Stereo type dan Labelling Terhadap Perempuan Pada Berita “19 Detik Gisella Anastasia” di Portal Okezone.com dan Kompas.com - Tiara Angelica; Reni Nuraeni (Universitas Mercu Buana, 2022)
In November 2020, public attention was drawn to the immoral video issue involving the artist Gisella Anastasia. The case is synonymous with the term